Laparoscopic colectomy with transanal ileal descent in a singles surgical stage for the treatment of ulcerative colitis - Mejìa Camacho David; Jiménez Urueta Pedro Salvador; Suárez Gutiérrez Roberto (Instituto Nacional de Pediatría, 2014)
Ulcerative colitis (UC) is an inflammatory disease of the rectal and colonic mucosa and submucosa. Some patients may require surgical treatment. Classically colectomy and ileostomy is recom- mended as a first stage and ileoanal anastomosis in a second surgical stage. We report the case of a patient with UC treated with laparoscopic total colectomy and ileoanal anastomosis in a single surgical stage.